IMPACTO DA DISPNEIA NA QUALIDADE DE VIDA DE OBESOS SUBMETIDOS À CIRURGIA BARIÁTRICA - Hernandez, Nathaly Marin (2018)
Obesity is associated with many comorbidities, especially those related to pulmonary function, such as dyspnea. As a result, many obese individuals seek for bariatric surgery (BS), which can generate satisfactory results in the health conditions and quality of life (QoL) of this population. However, no studies evaluating dyspnea and its impact on QoL in obese individuals submitted to BS were found. The objective of the present study was to evaluate the occurrence of dyspnea and its impact on QOL in obese individuals submitted to BS. This longitudinal study evaluated SB outcomes before the procedure and in the periods of 1 month and 6 months after surgery. The data collected from 104 participants were sociodemographic, anthropometric, comorbidities, dyspnea (modified Borg scale and modified dyspnea scale), quality of life related to breathing (QOLRB) (AQ20-R questionnaire), QoL (SF-36 questionnaire), and oral health-related quality of life (QHRQoL) (OHIP-14 questionnaire). Article 1 aimed to determine the prevalence of dyspnea and associated factors in obese individuals who sought for BS, using preoperative cross-sectional data. The results showed that the prevalence of mild, moderate, and severe dyspnea was of 43.3%, 35.6%, and 4.8%, respectively. After adjustment, morbidly obese individuals suffering from depression presented approximately 3 and 4 times greater chance, respectively, of the occurrence of dyspnea. Article 2, also transversal, aimed to evaluate the impact of dyspnea on QOLROH after adjustment for confounding variables. OHIP-14 scores were low in obese individuals. In the multivariate analysis, total OHIP-14 scores were 3.91-fold higher in participants with shortness of breath. All domains were associated with dyspnea, with the exception of physical and psychological disabilities. Article 3 explored the longitudinal data and determined the effect of BS on dyspnea and its impact on QoL. The prevalence of dyspnea was of 40.4%, prior to BS, presenting a significant and gradual reduction after 1 month (17.4%) and 6 (1.54%) months of surgery (P<0.001). QOLRB also reduced systematically (P <0.001). There were statistically significant differences between the individuals with and without dyspnea on the AQ20-R and the SF-36, in the preoperative period (P = 0.004), and after 1 month (P = 0.041) on BS. After the adjustment for covariates, the associations between dyspnea and QoL remained significant. It can be concluded that the reduction of the body weight of BS provided a reduction in dyspnea and that it had a negative impact on the general QoL, QOLRB and QHRQoL, even after adjustment. Thus, the results of this study reinforce the importance of the treatment of dyspnea with harm reduction policies, concomitantly with the reduction of body weight and other comorbidities in health, to improve the QoL of obese individuals submitted to BS.